2007
DOI: 10.1002/hyp.6246
|View full text |Cite
|
Sign up to set email alerts
|

Water fluxes at a fluctuating water table and groundwater contributions to wheat water use in the lower Yellow River flood plain, China

Abstract: Abstract:Capillary upflow from and deep percolation to a water table may be important in crop water supply in irrigated areas of the lower Yellow River flood plain, north China. These fluxes at the water table and the variations of the capillary upflow in relation to crop evapotranspiration need to be investigated to quantify the effect of a water table on soil water balance and to improve agricultural water management. A large weighing lysimeter was used to determine daily crop evapotranspiration, daily capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…The quantification of upward fluxes from a shallow groundwater table is a significant topic that has been extensively researched (Ganiev, 1979;Zhang et al, 1999;Soppe and Ayars, 2003;Kahlown et al, 2005;Babajimopoulos et al, 2007;Yang et al, 2007;Huo et al, 2011). In the Fergana Valley, Ganiev (1979) studied over a period of four years the capillary rise from a shallow water table in lysimeter experiments under fallow and natural conditions, and cropped with cotton or alfalfa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of upward fluxes from a shallow groundwater table is a significant topic that has been extensively researched (Ganiev, 1979;Zhang et al, 1999;Soppe and Ayars, 2003;Kahlown et al, 2005;Babajimopoulos et al, 2007;Yang et al, 2007;Huo et al, 2011). In the Fergana Valley, Ganiev (1979) studied over a period of four years the capillary rise from a shallow water table in lysimeter experiments under fallow and natural conditions, and cropped with cotton or alfalfa.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the same region, maize and sorghum were found to be sensitive to waterlogging, and crop yields were reduced with a rise of the groundwater table. Yang et al (2007) quantified water fluxes in large weighing lysimeters, with a fluctuating groundwater table between 1.6 and 2.4 m during the wheat growth period and 0.7 and 2.3 m during the maize growth period, and found that, in a rotation system of wheat and maize, the cumulative capillary upward flux and the deep percolation were 89.6 and 55.9 mm, respectively. Liu and Luo (2011) conducted a lysimeter experiment to quantify the effects of shallow water tables on the water use and yield of winter wheat under rainfed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The actual ET was either measured directly in the SI fields, or obtained from crop water usage based on location, crop type, and the emergence date (NDAWN, 2016), or adjusted from reference ET but based on water table and soil moisture changes in the field using procedures proposed in Kolars (2016) and Yang et al (2007). The precipitation was measured by a standard rain gage at the site.…”
Section: Water Application Efficiencymentioning
confidence: 99%
“…If the evapotranspiration rate is measured in the irrigated field, it can be used to represent the field water usage. However, when actual ET was not measured, if other data, such as soil moisture or water table data were measured, the water consumption can be estimated indirectly (Yang et al, 2007;Kolars, 2016).…”
mentioning
confidence: 99%
“…The surface area of 3.14 m 2 was used to calculate ET from the lysimeter, which may be smaller than the actual effective area of the lysimeter, especially during the middle to later growth stages and result in overestimation of ET, as discussed by Allen et al (2011). A detailed description of the lysimeter experiment was given by Yang et al (2007). Winter wheat (variety Zhixuan 1) and maize (variety Yedan 22) were planted in 9 61 104 29 9 39 Nov. 0 11 0 4 0 18 Dec. 0 0 0 2 13 7 Jan. 0 12 40 3 4 4 Feb. 0 12 25 0 1 7 Mar.…”
Section: Lysimeter Experiments and Data Measurementsmentioning
confidence: 99%